(untitled) (Journal of Plant Disease Sciences, 2018)
Effect of fungicides, chemical, oils, wax and bio-agent against postharvest pathogens of mango was evaluated for their inhibitory effect in vitro. Carbendazim @ 0.1 % was recorded cent per cent growth inhibition of Colletotrichum gloeosporioides and also achieved highest mycelial growth inhibition (52.96%) of Alternaria alternata followed by Benomyl @ 0.05% (48.89%). Carbendazim @ 0.1%, Benomyl @ 0.05%, Benomyl @ 0.05% + Potassium sorbate @ 2% and Hydrogen peroxide @ 10% restricted the complete mycelial growth (100%) of Aspergillus Niger. Saccharomyces cerevisiae @ 109 cells/ml was the next best treatment with 44.86 per cent growth inhibition.